Proceedings of the 3rd International Conference on Multimedia Technology (ICMT 2013) - Farag, Aly A.; Yang, Jian.; Jiao, Feng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Proceedings of the 3rd International Conference on Multimedia Technology (ICMT2013) focuses on both the theory and applications of multimedia technology. The recent advances, new research findings and applications in the fields of theoretical, experimental and applied image & video processing and multimedia technology presented at the conference are brought together in this book. It will serve as a valuable reference for scientists and engineers working in multimedia and related fields. Prof. Aly A. Farag works at the University of Louisville, USA; Prof. Jian Yang works at Tsinghua University, China; Dr. Feng Jiao works at Nanjing University of Information Science & Technology, China.
Multimedia Tools and Systems -- Image Processing Technology -- Network Applications -- Multimedia Entertainment Service.
Keywords: Computer science; Multimedia systems; Computer vision; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Signal, Image and Speech Processing; Multimedia Information Systems